2007
DOI: 10.2193/2006-123
|View full text |Cite
|
Sign up to set email alerts
|

Using Vaginal Implant Transmitters to Aid in Capture of Mule Deer Neonates

Abstract: Estimating survival of the offspring of marked female ungulates has proven difficult in free-ranging populations yet could improve our understanding of factors that limit populations. We evaluated the feasibility and efficiency of capturing large samples (i.e., .80/yr) of neonate mule deer (Odocoileus hemionus) exclusively from free-ranging, marked adult females using vaginal implant transmitters (VITs, n ¼ 154) and repeated locations of radiocollared females without VITs. We also evaluated the effectiveness o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
77
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(82 citation statements)
references
References 26 publications
5
77
0
Order By: Relevance
“…We conducted fawn searches from late May through late August in 2004–2006 because white‐tailed deer birthing peaked near 20 June and mule deer birthing peaked 1 month later (Haskell et al ). We used vaginal implant transmitters (VIT) to help locate birth sites and capture true neonates <24 hours postpartum (Carstensen et al , Bishop et al , Haskell et al , Tatman et al ). We monitored very high frequency (VHF) signals of VITs daily from the ground between 0001–0700 hours to preclude false‐negative signals caused by direct sunlight on heat switches of expelled VITs (S. P. Haskell, personal observation).…”
Section: Methodsmentioning
confidence: 99%
“…We conducted fawn searches from late May through late August in 2004–2006 because white‐tailed deer birthing peaked near 20 June and mule deer birthing peaked 1 month later (Haskell et al ). We used vaginal implant transmitters (VIT) to help locate birth sites and capture true neonates <24 hours postpartum (Carstensen et al , Bishop et al , Haskell et al , Tatman et al ). We monitored very high frequency (VHF) signals of VITs daily from the ground between 0001–0700 hours to preclude false‐negative signals caused by direct sunlight on heat switches of expelled VITs (S. P. Haskell, personal observation).…”
Section: Methodsmentioning
confidence: 99%
“…We used trans‐abdominal ultrasonography (SonoSite 180™; L38/10–5 MHz transducer; SonoSite, Inc., Bothell, WA) to determine pregnancy (Bishop et al 2007) and estimate maximum rump fat depth (MXF; Cook et al 2001) to the nearest 0.1 mm, as described by Stephenson et al (1998). Generally, our ultrasound pregnancy observation time was ≤5 minutes.…”
Section: Methodsmentioning
confidence: 99%
“…Vaginal implant transmitters (VITs) are radio transmitters inserted into the vaginal canal of a female ungulate and held in place by flexible silicone wings to be expelled at parturition. Use of VITs can improve precision and accuracy in determining parturition timing and location, resulting in better estimates of juvenile survival (Carstensen et al , Bishop et al , Haskell et al , Tatman et al ). Vaginal implant transmitters have been used for a variety of ungulates including mule deer ( Odocoileus hemionus ; Johnstone‐Yellin et al , Bishop et al , Haskell et al ); Columbian black‐tail deer ( O. h. columbianus ; Pamplin ); white‐tailed deer ( O. virginianus ; Haskell et al ); elk ( Cervus elaphus ; Vore and Schmidt , Johnson et al ); and bighorn sheep ( Ovis canadensis ; Smith et al ; Table ).…”
Section: Summary Of Vaginal Implant Transmitter Studies and Transmittmentioning
confidence: 99%
“…These first‐generation VITs were surgically sutured into mule deer, which frequently caused localized trauma and increased infection risk (Garrott and Bartmann , Barbknecht et al ). Eventually, VITs were equipped with flexible wings to secure them in place, eliminating the need for suturing, and greater wing width improved retention of VITs (Bishop et al , Haskell et al ). Antenna clipping (i.e., shortening) became standard practice to prevent ungulates (primarily white‐tailed and mule deer) from removing transmitters with their teeth (Seward et al , Haskell et al , Barbknecht et al , Tatman et al ); although this behavior has only been documented once, by Carstensen et al () who found bite marks on one VIT antenna post‐expulsion.…”
Section: Summary Of Vaginal Implant Transmitter Studies and Transmittmentioning
confidence: 99%
See 1 more Smart Citation